Sustainability Of Small Medium Enterprises And Economic Growth: A Meta Analysis - Aqil Teguh Fathani; Novia Amirah Azmi; Annisa Weriframayeni (Cita Konsultindo Research Center, 2022)
This study was conducted to determine the thematic trends of Small and Medium Enterprises (SMEs) and Economic Growth research, which focuses on policies, governance, communication patterns, and strategies. The research questions have been made more concrete by applying structure and bibliometric analysis to provide additional information that is not yet fully understood or analyzed; 1) What is the relationship between the topics of SMEs and economic growth, and how are they grouped? (2) What key themes have been used to promote SMEs and economic growth for the greater good of society? The research material of 224 documents is drawn from the Scopus database and covers the topics